1994
DOI: 10.1210/jcem.79.1.8027227
|View full text |Cite
|
Sign up to set email alerts
|

Oral iodized oil for correcting iodine deficiency: optimal dosing and outcome indicator selection.

Abstract: Oral iodized oil is the major alternative to iodized salt for correcting endemic iodine deficiency. This study responds to a need for better guidelines in its use. Schoolchildren, aged 6-11 yr, from a severely iodine-deficient area of Algeria received iodized poppy seed oil (Lipiodol) in a single oral dose containing 120, 240, 480, or 960 mg iodine (groups A-D) or in an im injection of 480 mg iodine (group E). Thyroid volume by ultrasonography had not changed 395 days after treatment in groups A, B, and C, had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 11 publications
2
42
1
3
Order By: Relevance
“…Goiter prevalence decreased rapidly and thyroid function reverted to normal and remained so for up to 7 years after injections of iodized oil and for up to 1 to 2 years after oral administration (47)(48)(49)(50)(51)(52)(53). Key factors in this success were normalization of the thyroid's iodine stores (48) and the level of iodization of thyroglobulin, the determining factor in impairment of thyroid function (36).…”
Section: Current Status Of Idd Control Programs: Public Health Issuesmentioning
confidence: 99%
“…Goiter prevalence decreased rapidly and thyroid function reverted to normal and remained so for up to 7 years after injections of iodized oil and for up to 1 to 2 years after oral administration (47)(48)(49)(50)(51)(52)(53). Key factors in this success were normalization of the thyroid's iodine stores (48) and the level of iodization of thyroglobulin, the determining factor in impairment of thyroid function (36).…”
Section: Current Status Of Idd Control Programs: Public Health Issuesmentioning
confidence: 99%
“…However, only few studies have been made on the consequences of increasing the iodine intake in a population in relation to correction of iodine deficiency to optimal iodine nutrition. Some of these studies have found an association between the increase in iodine intake and an increase in the incidence of hypothyroidism [4][5][6], but not all studies have found this association [7,8]. The mechanism behind the effect could be an inhibitory effect of iodine on the thyroid [9], or that iodine induces autoimmunity in genetically predisposed persons [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In a more recent 5-year Brazilian study, it has been reported that excessive iodine intake may have increased the prevalence of TAA 5.6 times and hypothyroidism 6.6 times when compared with patients from low iodine intake area [29]. This association may be due to iodine-induced increase in the immunogenicity of the thyroglobulin molecule [30,31]. However, some other studies have failed to find a correlation between iodine intake and the prevalence of TAA which could not support the notion that excessive iodine intake may not be the only factor to cause TAA [31][32][33][34].…”
Section: Discussionmentioning
confidence: 98%
“…This association may be due to iodine-induced increase in the immunogenicity of the thyroglobulin molecule [30,31]. However, some other studies have failed to find a correlation between iodine intake and the prevalence of TAA which could not support the notion that excessive iodine intake may not be the only factor to cause TAA [31][32][33][34]. Moreover, a recent report by Zeitlin et al [35] indicated that 50% of patients with TAA have a family history, suggesting that, under specific environmental conditions, individuals who are genetically predisposed may develop TAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation